Estudo numérico do efeito de propriedades mecânicas e do atrito no fenômeno de shakedown - Gonçalves, Rodrigo Pereira (2016)
Materials subjected to cyclic loading can initially respond plastically and,after a certain amount of load cycles,begin to have a perfectly elastic response. This transition in behavior is called shakedown. One of the applications that can benefit from a shakedown analysis is the wheel-rail contact of a railroad. A shakedown diagram relating load and friction can be used to predict the response of materials in contactin various conditions, allowing the choice of parameters that meet the needs of the railway, ensuring good braking and load capacity, combined with good service life of rails and suitable fuelconsumption. This work is intended to be an initial study of shakedown in the wheel-rail contact. To this end, it aims to carry out a numerical study of the influence of different mechanical properties and friction in the shakedown phenomenon considering thecase of a sphere-plan contact submitted to unidirectional cyclic loading. Commercial software ABAQUS was used in order to simulate the cyclic loading ofaxisymmetric elements, rigid sphere on a deformable half-space,using thefinite element method. Analyses considered theeffects of yield stress, friction coefficient, degree of strain hardening and the strain hardening model. Results indicate that the more resistant the material (higher yield stress), the faster the shakedown stabilization. For the conditions studied,friction isdetrimental to the shakedown event, increasing the amount of loading cycles required for its stabilization. Strain hardening hasa beneficial influence, facilitating the occurrence of the phenomenon.The isotropic and linear kinematic hardening models proved to be inadequate to reproduce conditions thatinvolve high plastic deformation, preventing the prediction ofincremental plasticity. The non-linear kinematic hardening model was adequate for shakedown analysis in all simulated conditions